Nurturing a New Industry Rooted in Geoscience: Stakeholder Insights on Minewater Thermal in Scotland - K. B. Deeming; J. Dickie; J. J. Roberts; Z. K. Shipton (Earth Science, Systems and Society)
Heat decarbonisation is crucial for climate action and the transition to a sustainable society. Abandoned, flooded mines can be used to provide low-carbon heating and cooling for buildings or as thermal energy storage for district heating networks (“minewater thermal resources”). Due to the capital-intensive nature of the infrastructure required for minewater thermal, its use should be considered early in project development. Developers therefore need to be aware of the full range of low-carbon heating solutions to implement the most sustainable solutions. Through interviews with twelve key stakeholders in Scotland, this study aims to determine the level of awareness of this technology among stakeholders who require heat for their developments, and stakeholders who would be involved in the development or construction of such schemes. Our findings have implications for how the geoscience community could aid the development of a minewater thermal industry. Stakeholders perceived a range of advantages of minewater, including use as thermal storage and the co-location of minewater resources with heat demand. Perceived disadvantages included the high capital cost and pre-construction risks associated with determining the feasibility minewater resources. Building trust and confidence in minewater thermal technology was identified as a key factor for success. Issues relevant for low-carbon heat in general were also raised including, high retail cost of electricity, skills gaps and labour shortages. Geoscientists can identify prospective minewater resources and assess the risks associated with exploration, development and operation of that resource, contributing to building confidence and reducing up-front capital costs. Given the multidisciplinary nature of the heat decarbonisation challenge, geoscientists must be able to communicate clearly and transparently about the science underpinning resource estimates and risk mitigation measures. For minewater thermal projects to succeed, geoscientists must be equipped with skills, knowledge and understanding to embrace these wider roles in nurturing this nascent industry.